Unpacking "Sexting": A Systematic Review of Nonconsensual Sexting in Legal, Educational, and Psychological Literatures. (December 2017) - Krieger, Michelle A.
Concerns about sexting are increasingly prevalent in mainstream and academic media despite limited and inconsistent research findings about the practice. Much of this discourse centers around harm and sexting is commonly considered to be a risky behavior. A driving factor in these discussions is the apparent conflation of consensual and nonconsensual acts or sexting behaviors. A systematic review was conducted to determine the extent to which consensual and nonconsensual acts were conflated in the legal, educational, and psychological literatures on sexting, and how nonconsensual sexting was conceptualized within these disciplines. Definitions of sexting varied widely with regard to the inclusion or exclusion of nonconsensual acts. Nonconsensual acts were conceptualized in the following ways: as a risk of sexing, as being the fault of the victim, as bullying, or as a form of violence against women. Implications for research and practice are discussed.